TRIADIC PATTERN TOTAL THEATRE AS A MODEL FOR THEATER DIRECTING METHODS BASED ON THE CONSTRUCTION OF TRIANGTU SUNDANESE PHILOSOPHICAL VALUES - Rusmana, Tatang (International Review of Humanities Studies, 2023)
The three basic values of the philosophy of life belonging to the culture of the Sundanese people in Indonesia are the principles of triadic patterns of life contained in the Tritangtu Sunda philosophy. The three basic philosophical values contain a view of the division of triadic worlds, namely Buana Nyungcung (upper world, metaphor; sky, water, and women), Buana Larang (underworld, metaphor; earth, land, and men), and Buana Pancatengah ( Middle world, metaphor; stone, human, male and female, and life behavior). Tritangtu Sunda is a cosmic perspective of the unification of three interconnected worlds in the life of the Sundanese people. The union is the marriage between Buana Nyungcung and Buana Larang, and Buana Pancatengah which is the center of their connection. Tritangtu Sunda's philosophy of life which contains the construction of cultural and artistic values is used as a model for the directing method; Triadic Pattern Total Theater Performance. Research and concretization of method models are realized through a transformation process, to find new creations or new forms of change both in function and structure. "To transform", means to create something new that has never existed before. Transformation can mean a change in “mindset”. The research tools used Environmental theater theory and Performance Theory suggested by Schechner (1994 and 2004).